Development of the E-Muhadatsah Kit for Non-Arabic Speakers in Malaysian Institutions of Higher Learning: A Need Analysis - Borham, Siti Rahmah; Ramli, Saipolbarin; Abdul Ghani, Mohammad Taufiq; Borham, Abd Shakor (Journal of Techno-Social, 2022)
Needs analysis plays an important role in the development of a product to ensure that the product can meet the needs of consumers. The development of the E-Muhadatsah kit or Arabic conversation kit based on an android application is a self-communication platform among non-Arabic speakers in Malaysian Institutions of Higher Learning. This study aims to identify the need for developing the E-Muhadatsah kit among non-Arabic speakers at the tertiary level as well as to identify the level of interest in Arabic speaking, Arabic communication confidence, and students’ willingness to communicate in Arabic. The assignment and exercise needs in improving students’ Arabic speaking or communication skills were also identified. A set of questionnaires was distributed to 214 respondents from universities in Malaysia namely UPM, UPSI, UniSZA, and UiTM. Then, the data obtained from the administration of the questionnaire were analyzed using SDSS version 25 software and interpreted based on the analysis of mean scores and standard deviations. Meanwhile, the open-ended questionnaire data were analyzed thematically. The results showed that respondents saw the development of the E-Muhadatsah kit as a great need for non-Arab students in higher education. In addition, the study also found that respondents showed a high interest in Arabic speaking, confidence in Arabic communication, and students’ willingness to communicate in Arabic at a high level. Thus, this study proposes the development of a conversation-based Arabic language interactive multimedia kit to improve the communication proficiency of non-Arabic speakers, further able to help Arabic language educators to diversify multimedia-assisted teaching methods.